Pemodelan Persamaan Struktural dengan Analisis Linear Structure Relationship (Lisrel) - Hutabarat, Ida Mariati (Department of Mathematics Education, Faculty of Mathematics and Natural Sciences, UNY, 2008)
The structural equation modeling is a part of statistics which can be used to analyze relation which is developed through one or more dependent variable which is explained by one or more independent variable, and at the same time one or more independent variable acts as an independent variable for the other dependent variable. In the covariance structure based structural equation modeling the analysis which is frequently used is the Linear Structure Relationship (LISREL) analysis. The aim of this study is to learn the accuracy and consistence of the estimated values of parameters of structural equation model using LISREL analysis. The difference between one path coefficient and another shows the difference of closeness level of the relationship between the independent variables and the latent variables in an expected block.